(untitled) (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted on sweet orange cv. Sathgudi to study the effect of urea and zinc, alone and in different combinations, on growth, yield and quality of Sathagudi sweet orange during the year 2002 and 2004 under semi- arid conditions of Panchmahals district of Gujarat. Treatments comprised of zinc as foliar spray (0.5%) alone and in combination with different nitrogen doses in the form of urea in soil as well as foliar spray. Soil application of urea was given in the last week of June and first week of September during both the years of experimentation. Results of the experiments revealed that the growth of plants in terms of plant height, stem girth and plant spread, yield in terms of weight of fruits, fruit size, and quality with respect of juice content, TSS, total sugar and vitamin C increased with the soil application of urea 350 g per tree over control. The parameters further showed an increasing trend when urea was sprayed in addition to soil application. An increase in the percentage of urea in solutions for spray from 0.5 to 1.5% increased the growth, yield and quality of sweet orange fruits. Among the various treatment combinations evaluated, urea in soil (350 g) + zinc (0.5%) +Urea as foliar spray (1.5%) was found to be the best to increase the growth and yield of quality fruits under semi-arid ecosystem of western India.